Post IPY Middle Atmosphere Temperatures from Rayleigh Lidar in Alaska 2011-2014 ... - Collins, Richard (NSF Arctic Data Center, 2015)
This data set contains files of individual atmospheric temperature profiles from 40-80 km measured at Poker Flat Research Range (PFRR), Chatanika, Alaska (65.1 N, 147.5 W). The temperature profiles are retrieved from lidar echo data using standard retrieval methods that employ downward data integration under the assumption of hydrostatic equilibrium. The initial temperature at 80 km is taken from the Stratosphere-troposphere Processes And their Role in Climate (SPARC) Reference Atlas. The PFRR data is available as ASCII files at http://wdcvpa.gi.alaska.edu/. The PFRR data is available as NetCDF files at this site. This NetCDF data is identical in retrieval algorithm and format to the data of project "Pan-Arctic Studies of the Coupled Tropospheric, Stratospheric and Mesospheric Circulation" ...